Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene